Strategies and Role of Parents on Language Acquisition of Children with Special Needs - Wardani, Esti Tri; Siregar, Iskandarsyah; Susanto, Arju; Hamzah, Nurul Huda (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
Parents play a significant role in the language acquisition process of children with special needs. This study aims to reveal the strategies and roles parents play in supporting the language acquisition process of children with special needs, which should be implemented in educating children at home. In this study, subjects were children with special needs diagnosed with autism and intellectual disability, with parents acting as resource persons. This research uses descriptive qualitative techniques with triangulation techniques as data collection methods and analysis using behavioristic theory. As a result, in supporting the language acquisition process of children with disabilities, parents face challenges, provide appropriate treatment, and create effective strategies for dealing with language acquisition challenges. There are six challenges in supporting children with language acquisition: communication, social stigma, learning consistency, limited resources, social interaction, and emotions and psychology. The resulting treatments and strategies provide actions used to deal with these challenges.